PENGARUH INDOL-3-BUTIRIC-ACID DAN THIDIAZURON TERHADAP MULTIPLIKASI TUNAS NENAS (Ananas comosus (L) Merr) CV. SMOOTH CAYYENE SECARA IN VITRO - Syafii, Mohammad; Badami, Kaswan; Nursandi, Fatimah (Rekayasa, 2013)
Pineapple (Ananas comosus L.) is one of the most potential fruit crop cultivating in Indonesia. However, it is difficult to meet the demand for planting materials using the conventional propagation techniques due to production inefficiency. This research aim to know the influence solid medium of Murashige and Skoog (MS) composed of Indol-3-Butiric Acid and Thidiazuron, upon pineapple Var Smooth Cayenne shoot multiplication response. Shoot multiplication using a factorial complete random design. The first is a 3-level IBA concentration (0.3 ppm, 0.6 ppm, 0.9 ppm), a 3-level TDZ concentration (0.2 ppm, 0.4 ppm, 0.6 ppm). The finding shows that MS richly composed IBA and TDZ with low concentration gives 100% shoot the fastest periodic appearance (two weeks after incubation). Varians analysis finding shows that there is no interaction between IBA and TDZ.Low IBA concentration gives the higest quantity of shoot 9.32 (5.60 data transformation) at 5 week after incubation, at the end of the analysis tends to give the higest shoot 11.17 (6.18 data transformation) even though it is statistically not slighty difference. The highest TDZ concentration (0,6 ppm) give a few number of roots 0.89 (2,65 data transformation) and the lowes shoots leaf 3.84 (4.04 data transformation). The higher the TDZ is, the more nodal may appear.